COVID-19 exposes weaknesses in public health in the Peruvian Amazon and highlights opportunities for a One Health approach - Ormea, Verónica (2023)
The Amazon is home to important wildlife and a biodiversity hotspot of global importance. The ancestral knowledge kept by Indigenous communities about its fauna and flora contributes further to its irreplaceable value. The Peruvian Amazon was heavily struck by the COVID-19 epidemic with a cumulative incidence of 725, a mortality rate of 34 per 100,000 inhabitants, and a case fatality rate of 4.6% by the end of July 2020. In this work, we review scientific literature and media to trace the events that happened at the beginning of the COVID-19 epidemic in the Peruvian Amazon. Results are synthesized in three observations: (1) the evolution of the COVID-19 epidemic within the Peruvian Amazon and the response of the Peruvian health care system, (2) Confusing information about Ivermectin use for COVID-19 treatment and prevalent self-medication (3) The response of the traditional Indigenous health care system to the COVID-19 epidemic. These three observations are interdependent. There is an unexploited potential for integrative approaches linking traditional medical practices (TMP) and biomedical approaches and they may benefit from the interactions that occur between them. Synergies can also be explored between the human and animal health care sector, especially in terms of the use and stewardship of medicines. We conclude that there is a benefit of the One Health approach in the region, which can go through the common ambition to improve the integrated health of people, animals and ecosystems, facilitate the enhancement of equity and inclusion while improving access to health services and conserving biodiversity.